An Assessment of Telecommunications Reform in Developing Countries - Fink, Carsten (World Bank, Washington, DC, 2014)
The authors analyze the effect of policy reform in basic telecommunications on sectoral performance using a new panel data set for 86 developing countries across Africa, Asia, the Middle East, and Latin America and the Caribbean over the period 1985 to 1999. The authors address three questions: 1) What impact do specific policy changes-relating to ownership and competition-have on sectoral performance? 2) How is the impact of change in any one policy affected by the implementation of the other, and by the overall regulatory framework? 3) Does the sequence in which reforms are implemented affect performance? The authors find that both privatization and competition lead to significant improvements in performance. But a comprehensive reform program, involving both policies and the support of an independent regulator, produced the largest gains-an 8 percent higher level of mainlines and a 21 percent higher level of productivity compared to years of partial and no reform. Interestingly, the sequence of reform matters: mainline penetration is lower if competition is introduced after privatization, rather than at the same time. The authors also find that autonomous factors, such as technological progress, have a strong influence on telecommunications performance, accounting for an increase of 5 percent a year in teledensity and 9 percent in productivity over the period 1985 to 1999.